Altered visual population receptive fields in human albinism. (July 2020) - Alvarez, Ivan; Smittenaar, Rebecca; Handley, Sian E.; Liasis, Alki; Sereno, Martin I.; Schwarzkopf, D. Samuel; Clark, Chris A.
Abstract: Albinism is a congenital disorder where misrouting of the optic nerves at the chiasm gives rise to abnormal visual field representations in occipital cortex. In typical human development, the left occipital cortex receives retinal input predominantly from the right visual field, and vice-versa. In albinism, there is a more complete decussation of optic nerve fibers at the chiasm, resulting in partial representation of the temporal hemiretina (ipsilateral visual field) in the contralateral hemisphere. In this study, we characterize the receptive field properties for these abnormal representations by conducting detailed fMRI population receptive field mapping in a rare subset of participants with albinism and no ocular nystagmus. We find a nasal bias for receptive field positions in the abnormal temporal hemiretina representation. In addition, by modelling responses to bilateral visual field stimulation in the overlap zone, we found evidence in favor of discrete unilateral receptive fields, suggesting a conservative pattern of spatial selectivity in the presence of abnormal retinal input.